2009
DOI: 10.1016/j.econmod.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal innovation-based growth and product market competition

Abstract: The influence of the degree of competition in the goods market on growth is analyzed by developing an endogenous growth model with horizontal innovation. Product market competition is measured by (1-Lerner index) and depends on both the share of factor inputs in total income and on the elasticity of substitution across goods. We find that the shape of the relationship between competition and growth can change dramatically according to which proxy of competition is used. We interpret our results in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Previous economic studies have proposed that R&D is engaged in improving the quality of products when product market competition gets more intense [44][45][46][47]. Bucci and Parello [48] found that the shape of the relationship between competition and growth can change dramatically according to which proxy of competition is used. However, the findings are not well applicable when contractors continuously pursue BCR as adverse feedback loops.…”
Section: The Market Competitive Behavior Under the Price-based Awardimentioning
confidence: 99%
“…Previous economic studies have proposed that R&D is engaged in improving the quality of products when product market competition gets more intense [44][45][46][47]. Bucci and Parello [48] found that the shape of the relationship between competition and growth can change dramatically according to which proxy of competition is used. However, the findings are not well applicable when contractors continuously pursue BCR as adverse feedback loops.…”
Section: The Market Competitive Behavior Under the Price-based Awardimentioning
confidence: 99%
“…Many researchers are trying to prove these views. Bucci and Parello (2009) and Cantner et al (2008) have arguments in line with Schumpeterian views.…”
Section: Innovation and Market Competitionmentioning
confidence: 72%
“…This argument is based on the idea that monopolists gain the advantage of their ability to prevent imitation so that the monopolists are freer to continue to innovate. This Schumpeterian view gets a lot of support (Cantner et al, 2008;Bucci and Parello, 2009).…”
mentioning
confidence: 97%
“…On contrary, Blundell et al (1999) empirically confirmed that competition enhances R&D activity in order to gain an advantage towards main competitors. During the last years, the idea of an inverse 'U-curve' dependence of innovative activities on the competition intensity has become popular (Bucci and Parello 2009). Previous empirical research based on survey data for Russia confirmed the existence of a 'U-relationship' (Kozlov and Yudaeva (2004)).…”
Section: Advanced Hypotheses and Data Descriptionmentioning
confidence: 93%